PWE-073 The Multidimensional Nature of Ibd Fatigue: A Systematic Review And Meta- Analysis. (4th June 2013) - Nathan, I; Fragos, K C; Forbes, A
Abstract : Introduction: Fatigue is recognised as a troublesome symptom for patients with IBD. There is no consensus regarding mechanisms driving fatigue or treatment. The aim of the present study is to assess the factors associated with IBD fatigue, using a systematic literature review and meta-analysis. Methods: A systematic literature review was performed in PubMed and EMBASE and additional articles and abstracts were identified by a hand search. All studies reporting correlation coefﬁcients (CCs) of fatigue with disease activity were included. A random-effects model was employed to produce a pooled estimate of CCs, which was the effect size in the current analysis. Fisher's Z transformation of the CCs was utilised for the analysis. Publication bias was assessed with funnel plots and Egger's test. All computations were executed with Stata 10.0 and MetaWin. Results: 23 studies were eligible for inclusion (total sample size = 5980). Fatigue was strongly correlated with IBD disease activity (pooled CC 0.386; 95% CI 0.335 to 0.435, range 0.165 to 0.540). Although there was no publication bias (failsafe N = 958), there was moderate heterogeneity (Q = 33.74, df = 14, p = 0.002; I² = 58.5%). Subgroup analysis showed a relationship between the correlation of fatigue and disease activity with population group (adult, paediatric) but not with country. Meta regression with percentage of males and mean age did not suggest that either were significant moderators of the particular correlation coefficient. Fatigue was also strongly correlated with quality of life (pooled CC –0.534; 95% CI –0.636 to –0.414), psychological distress (pooled CC 0.515; 95% CI 0.412 to 0.606) and daytime sleepiness (pooled CC 0.400; 95% CI 0.32 to 0.471), and was moderately correlated with anaemia (pooled CC 0.167; 95% CI 0.104 to 0.231) and social and functional impairment (pooled CC 0.288; 95% CI 0.133 to 0.424). Flare ups were not a significant predictor of fatigue (p > 0.05). Heterogeneity was present in all analyses (p < 0.05), except for the meta-analyses with anaemia, daytime sleepiness and social and functional impairment. Publication bias (assessed with the funnel plot) was more probable in the secondary factors compared with disease activity analyses in the initial correlation. Conclusion: A number of factors were found to correlate with IBD fatigue. These include: psychological distress, daytime sleepiness, disease activity, anaemia and social and functional impairment. This suggests both cognitive and physical aspects of IBD fatigue and clearly highlights the multidimensional nature of this symptom. This is part of a larger study conducted in collaboration with Crohn's and Colitis UK, King's College London and Addenbrookes' NHS Trust, funded by the Big Lottery Fund. Disclosure of Interest: None Declared.